Didaktične značilnosti učbeniških kompletov za pouk spoznavanja okolja po oceni učiteljev - Hus, Vlasta (Sodobna pedagogika, 2008)
Due to the curriculum modernization in primary school, the constructivistic theory of learning and teaching has become the main teaching theory in the subject of environment. It is reflected in the curriculum project and consequently, it should be taken into account also by the authors of textbook sets. There are several textbook sets for teaching the subject of environment published by different publishing-houses. With the empirical research, we tried to find out how the 3rd grade teachers evaluate textbook sets, from the point of view of the inclusion of particular elements of constructivism. The research has shown that teachers' evaluations are different. There is one publishing-house where these elements are more represented than in the other two since there is more individual pupils' work and because of evaluated forms, methods of work and pupils' activities, which lead to the development of higher pupils' mental processes.
Keywords: učbeniki; učni pripomočki; razredni pouk; spoznavanje okolja; osnovne šole; constructivism; konstruktivizem